Acute Pancreatitis Classifications: Basis and Key Goals. Issue 48 (December 2015) - Xu, Xiao Dong; Wang, Zhe Yuan; Zhang, Ling Yi; Ni, Rui; Wei, Feng Xian; Han, Wei; Zhang, Hui Han; Zhang, Ya Wu; Wei, Zhen Gang; Guo, Xiao Hu; Guo, Liu Qiang; Ma, Jian Zhong; et al.
Abstract : Abstract: To explore the efficacy of the revised Atlanta classification (RACAP) and the determinant-based classification of acute pancreatitis severity (DBCAPS) on the basis of clinical data and feedback from patients with acute pancreatitis (AP). The authors retrospectively investigated a total of 573 patients with AP admitted to our hospital between December 2011 and December 2014. The definitions of severity and local complications in AP using RACAP and DBCAPS are presented and common points and mutual differences between the 2 groups are analyzed and discussed. Classification according to RACAP and DBCAPS found 86 (15%) and 178 (31.1%) mild cases ( P  < 0 .01), 269 (46.9%) and 176 (30.7%) moderate cases ( P  < 0 .01), and 218 (38.0%) and 219 (38.2%) severe cases ( P  = 0 .95), respectively. A major contribution of DBCAPS is the introduction of a new type of severe AP, critical AP, identified in 4 patients (0.7%). Complications were observed in 313 RACAP-defined cases and 153 DBCAPS-defined cases ( P  < 0 .01). Among the 313 RACAP-defined cases, acute peripancreatic fluid collection (236 patients, 75.40%), pancreatic pseudocysts (20 patients, 6.4%), acute necrotic collection (42 patients, 13.4%), and walled-off necrosis (15 patients, 4.8%) were observed. Among the 153 DBCAPS-defined cases, sterile peripancreatic necrosis (105 patients, 68.6%), sterile pancreatic necrosis (44 patients, 28.8%), infected peripancreatic necrosis (2 patients, 1.3%), and infected pancreatic necrosis (2/153 patients, 1.3%) were observed. Both classifications adopted organ failure and complications as determinants of severity. Revised Atlanta classification refined local complications and DBCAPS modified severity to include critical AP. In accordance with the demands of precision medicine, a combination of the 2 could be important for further clinical practice and scientific research.